Отримання пластівців підвищеної харчової цінності з зерна голозерного вівса - Бажай-Жежерун, Світлана Андріївна; Береза-Кіндзерська, Людмила Василівна; Тогачинська, Ольга Василівна (My University, 2024)
Розроблено спосіб отримання пластівців підвищеної харчової цінності із голозерного вівса. Спосіб включає попередню підготовку зернової сировини, гідротермічне оброблення за холодного режиму: інтенсивне зволоження та тривале відволожування зернової маси. Після першого інтенсивного зволоження передбачено оброблення зерна інфрачервоним опроміненням. Наступними етапами є плющення, підсушування пластівців, провіювання, фасування. Досліджено вплив режиму оброблення на вміст основних вітамінів у зерні голозерного вівса. Визначено основні фізико-хімічні показники якості та харчову цінність вівсяних пластівців. Досліджено, мікробіологічну обсеміненість розробленого продукту

Whole grain products are an important component of the diet. Given the feasibility of treating grain with IR radiation, to improve its quality, we have developed a method for producing flakes of increased nutritional value from naked-grain oats. The method includes preliminary preparation of grain raw materials, hydrothermal treatment at low temperature regimes: intensive moistening and prolonged dehydration of grain mass. After the first moistening, the grain is treated with IR irradiation. The power of IR irradiation lamps is 230-260 W/m2, the distance from the grain placement plane to the lamp is 25-30 cm, and the duration of the process is 58-60 seconds. The next stages are flattening, drying, airing and packing. The influence of the treatment regime on the content of vitamins in the grain of naked-grain oats is investigated. The basic physic-chemical indicators of quality and nutritional value of flakes are determined. Microbiological insemination of flakes is within normal limits. Due to the consumption of 100 g of oat flaks, the daily need for nutrients can be provided: proteins - 23.8%, fats - 7.7%, carbohydrates - 26.3%, dietary fibers - 18.5%; vitamins: E - 18.5%, В1 - 52.3%, В2 - 25.0%
Keywords: голозерний овес; naked-grain oats; пластівці; харчова цінність; вітаміни; кафедра технології оздоровчих продуктів; flakes; nutritional value; vitamins